2021
DOI: 10.1186/s12985-021-01657-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced disease progression due to persistent HPV-16/58 infections in Korean women: a systematic review and the Korea HPV cohort study

Abstract: Background Persistent human papillomavirus (HPV) infection is a key factor for the development and progression of cervical cancer. We sought to identify the type-specific HPV prevalence by cervical cytology and assess disease progression risk based on high-risk persistent HPV infection in South Korea. Methods To investigate the HPV prevalence by Pap results, we searched seven literature databases without any language or date restrictions until July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Women with normal cytology and persistent HPV-16 infection have an approximately 30% chance of developing high-grade lesions in a 12-month period [ 50 ]. HPV-58 is also included in high-risk group and has been frequently reported in cervical cancer and high-grade lesions in several regions of the world [ 51 ], such as Asia [ 52 , 53 ], Mexico [ 54 , 55 ], Costa Rica [ 43 ], and Brazil [ 56 ]. Given the wide circulation of HPV-58 in the population studied and the evidence of its oncogenic potential, particular attention should be given to HPV-58 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Women with normal cytology and persistent HPV-16 infection have an approximately 30% chance of developing high-grade lesions in a 12-month period [ 50 ]. HPV-58 is also included in high-risk group and has been frequently reported in cervical cancer and high-grade lesions in several regions of the world [ 51 ], such as Asia [ 52 , 53 ], Mexico [ 54 , 55 ], Costa Rica [ 43 ], and Brazil [ 56 ]. Given the wide circulation of HPV-58 in the population studied and the evidence of its oncogenic potential, particular attention should be given to HPV-58 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that the most common HPV types are HPV-16 and HPV-58 among women with HSIL and cervical cancer [ 30 ]. Another study showed that persistent HPV-16 and HPV-58 infections are risk factors for cervical disease progression in Korea [ 31 ]. Our study also showed that HPV-58 was a common HPV subtype in women with HSIL, CIN3, and cervical cancer, second only to HPV-16.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study founded the most common HR-HPV genotypes infected Korean women at HSIL stages was HPV-16, followed by HPV-52, HPV-58, and HPV-33 [36]. Another study showed that persistent HPV-16 and HPV-58 infections are risk factors for cervical lesions in Korea [37].…”
Section: Correlation Of Hpv Genotypes With Cervical Lesionsmentioning
confidence: 96%